The Effects of Nigella Sativa (Black Seed) in Rhinosinusitis Subjects: A Systematic Review - Muhamad Najmi Muhamad Najemudin; Nurul Asyiqin Yusof (Journal of Pharmacy)
Introduction: Allergic rhinitis is a persistent inflammatory nasal condition triggered by an exaggerated immune response to allergens. Its primary complication is sinusitis which progresses to rhinosinusitis. Nigella Sativa known for its anti-inflammatory effects, has shown promising efficacy in treating rhinosinusitis. While various studies have reported Nigella Sativa's effects on rhinosinusitis, there is paucity in specifically addressing the optimal therapeutic dose and efficacy compared to conventional anti-histamine or anti-allergic drugs. Thus, this study aims to systematically review the effects of Nigella Sativa on rhinosinusitis in both human and animal subjects. Method: This systematic review followed the guidelines of PRISMA. A systematic literature search was performed through searches in PubMed, Scopus, Cochrane Library, and Google Scholar, along with the application of the snowball technique. Two authors independently evaluated the identified articles at various stages, including title, abstract, and full text, against predefined eligibility criteria. The assessment of potential bias in the studies incorporated the Joanna Briggs Institute (JBI) checklist for critical appraisal of human studies and the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) tool for assessing bias in animal studies. Results: Twelve studies were included in this study. Six studies were found to exhibit a low risk of bias, whereas three studies were categorized with a moderate risk of bias, and an additional three studies were identified as having a high risk of bias. Seven studies recorded significant symptom reduction while other studies showed better histological changes and chemical parameters compared with conventional medication. Conclusion: Nigella Sativa demonstrates anti-inflammatory, anti-histaminic, and antimicrobial properties, aiding in alleviating symptoms of allergic rhinitis and rhinosinusitis. 10 to 100 mg/kg/day Nigella Sativa is proposed to be considered as the optimum dose range as an alternative to conventional drugs such as montelukast, mometasone furoate, and dexamethasone due to its minimal side effects.